PROFITABILITAS USAHA AYAM PETELUR DI UD.PUNCAK JAYA JOMBANG DALAM UPAYA EFISIENSI KAPASITAS KANDANG - Al Kurnia, Dyanovita; Soedarto, Teguh; Sumartono, Sumartono (Berkala Ilmiah AGRIDEVINA, 2017)
The purpose of this research was to analyze profitability and technich, price, economicefficiency at Puncak Jaya firm. This research was done on April up to Mei 2016. Thekualitative method was applied in mechanism product of layer chickhen and analyze cobbdouglas profit function in profitability and production frontier in technich, price,economic efficiency. Sampling gathering was with purposive sample. The seconder datasto analyze cobb douglas profit function of profitability and production frontier oftechnich, price, economic efficiency. The result of this research was mechanism productof layer chickhen was influenced of  strain isa brown layer, feed for about 112 gr/day  toall of ages. Vaksin were used every two months. The employee were three men. Averageof egg productions were 487 kg per day. Shot scala profit was Rp.33.530.000 everymonth. The profit was negative influenced by DOC (Day Old Chick), Feed, Vaksin,medicine prices but price of employee was positive effect to profit. The technich, price,economic efficiency value were 1.72, 3.37 and 5.83. The efficiency value was more thanone. It means need production factor addition.